Implantable medical devices and healthcare affordability : exposing the spiderweb - West, Mark C.; Georgulis, Michael (New York : Productivity Press, 2023)
The United States spends more than 17% of its GDP on healthcare, while other developed countries average 8.7% of GDP on healthcare expenditures. All this spending doesn't equate to value, quality, or performance, however. Among 11 high-income countries, the United States healthcare industry ranked last during the past seven years in four key performance categories: administrative efficiency, access to care, equity, and healthcare outcomes. This book presents the implantable medical device (IMD) supply chain ecosystem as a microcosm of how these challenges of affordability and healthcare outcomes are created and are allowed to fester. The IMD Spiderweb, as the authors call it, is exposed as an example of how a wide range of participants--including physicians, health system CEOs, group purchasing organizations, health insurance companies, and supply chain executives--become ensnared in a web designed to benefit only one player. Health systems in the United States pay as much as six times more for some IMDs than their counterparts do in Europe, and prices for the same IMD model vary even among different U.S. hospitals. While there is a fascination with the latest and greatest device, there is also a shroud around visibility into how these products have performed and are likely to perform in patients. The costs continue to rise not only in healthcare expenditures, but also in death and disability. The IMD Spiderweb is presented as a prime lesson in the challenges in healthcare affordability and outcomes that occur throughout the entire healthcare industry. It is also put forward as an opportunity. The story behind how these challenges arose and continue to be deepened by the current healthcare ecosystem also provides a foundation for solutions.
OCLC-licensed vendor bibliographic record.
Keywords: Implants, Artificial; Medical care -- United States; Medical care, Cost of -- United States; Medical policy -- United States; BUSINESS & ECONOMICS / Distribution; BUSINESS & ECONOMICS / Industries / Manufacturing Industries